Rapid shifts in a marine fish assemblage follow fluctuations in winter sea conditions - Henriques, Miguel (2007)
Patterns of interannual variation are described for an inshore fish assemblage off the Arrábida rocky coast (Portugal). During an 11 yr period, the fish assemblage showed pronounced changes especially within its tropical, warm-temperate and cold-temperate elements. These changes followed a fluctuating pattern connected with the North Atlantic Oscillation (NAO) with a series of years where the modifications were slight, interspersed with years where faunal changes were very rapid, affecting up to 35% of the total number of species recorded in those years. After a transition year from a cold to a warm period or vice versa, the majority of the newcomers from the preceding phase were eliminated. Winter conditions, but not summer conditions, were good predictors of the observed patterns. Increases in sea surface temperature (SST) were associated with increases in the proportions of tropical and warm-temperate fish and with decreases in the proportion of cold-temperate elements, the reverse being true for decreases in SST. Interannual variation in faunal composition was not simply a consequence of changes in SST. Changes in other factors such as current flow direction and transport mechanisms, capable of bringing fishes from different biogeographical sources, may also play a role in the observed patterns. The influence of the NAO is therefore not only mediated by its effects on SST but also by the changes it induces in wind and current patterns along the Portuguese shore. Long-term trends caused by persistent changes, like those involving global warming, may be masked by the fact that at an intermediate time scale, faunal changes are characterised by a succession of oscillations rather than by a steady modification in a single direction. This outlines the importance of long-term monitoring data, since short-term studies may only capture single phases of a complex oscillation, giving a false picture of the overall pattern of change.